Educommunication in nutrition and neurodegenerative diseases: a scoping review protocol - Kenio Costa Lima; Karla Monica Dantas Coutinho; Sancha Helena de Lima Vale; Lucia Leite-Lais; Manaces Santos Bezerril; Monica Karina Santos Reis (BMJ Open)
Introduction Neurodegenerative diseases affect the nervous system and are characterised by the deterioration and/or death of neurons. Nutrition care is essential for maintaining an adequate nutritional status, which influences the prognosis and survival of patients with neurological diseases. Caregivers participate assiduously in the care of these patients and must be integrated into the multidisciplinary team. They often need specific training or knowledge regarding food and nutrition to perform their roles with patients. Health educommunication is a learning tool that can positively influence the appropriation of the theme and the construction of care autonomy. This scoping review (ScR) will map educommunication actions/strategies in nutrition and neurodegenerative diseases.Methods and analysis This ScR will be designed based on the methodology of Arksey and O'Malley and will follow the methodological guidance for conducting a Joanna Briggs Institute ScR. The research question addressed by the scoping review will be: what actions/strategies for educommunication in nutrition and neurodegenerative diseases have been developed for patients or caregivers? Many search sites it will be used in this review, such as electronic databases (Embase, PubMed/MEDLINE, Scopus, Web of Science), Google Scholar and grey literature sources. No restrictions of date or language will be applied to the search strategy. Two reviewers will independently screen all abstracts and full-text studies for inclusion. Data, including the study design, objective, study population, neurodegenerative diseases, nutrition topics and educommunication strategies will be logically organised and tabulated in Microsoft Excel.Ethics and dissemination The data used for this review are from secondary sources and available to the public; thus, no ethical approval and human consent will be required for this study. Dissemination of the results will be published in a peer-reviewed journal and presented at conferences.